PENINGKATAN HASIL BELAJAR PKN MATERI BERORGANISASI MELALUI METODE GALLERY WALK DI KELAS V B MI DARUN NAJAH SIDOARJO - Najah, Amirotun (Journal Of Islamic Elementary School (JIES), 2019)
This study aims to determine the application of the Gallery Walk method and increase the learning outcomes of students in PKn subject matter after using the Gallery Walk method in class V B MI Darun Najah Kwangsan Sedati Sidoarjo. This research is a classroom action research using the Kurt Lewin model. The data of this study were obtained by interviews, observation, documentation, written tests and non-tests. The results of the study show: The application of the Gallery Walk method to improve the material for organizing Civics subjects in class V-B MI Darun Najah Kwangsan Sidoarjo can be well implemented. This is evidenced by the activities carried out by the teacher experiencing an increase from the first cycle of 83 to 94 in the second cycle. For student activities the increase in the second cycle amounted to 93 from the previous only 76 in the first cycle. Increased learning outcomes of students organizing material PKn subjects after using the Gallery Walk method is characterized by class average scores and increased learning outcomes in each cycle. The class average at the pre cycle is 69, increasing in the first cycle to 78 and the second cycle increasing again to reach an average of 84. The percentage of completeness of student learning outcomes in the first cycle of 45% increased to 86% in the second cycle.